2017
DOI: 10.1038/eye.2017.88
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of symptoms experienced by persons with dry eye disease while driving in China

Abstract: PurposeTo assess the vision-related quality of life and self-reported driving performance of patients with dry eye disease (DED).Patients and methodsThe study was performed in the eye centre of Peking University Third Hospital, China. In total, 87 dry eye patients and 42 controls were enroled, including 49 patients without any treatment (group A), 38 patients treated with artificial tears (group B) and 42 controls without DED (group C). The participants had no eye disease other than DED. Scores of a vision-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
4
0
2
Order By: Relevance
“…3,49,50 Patients with DED experience impairments in workplace performance as well as in many other daily activities such as reading, driving, cooking, using a computer, and watching TV. 3,[49][50][51][52][53] Notably, a longitudinal study of patients with no diagnosis of depression or anxiety prior to receiving a diagnosis of DED found that with DED treatment, improvements in DED symptoms correlated with improvements in psychological symptoms. 31 In these patients whose psychological symptoms improved when their DED symptoms improved, the burden of living with DED symptoms may have been contributing to their depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…3,49,50 Patients with DED experience impairments in workplace performance as well as in many other daily activities such as reading, driving, cooking, using a computer, and watching TV. 3,[49][50][51][52][53] Notably, a longitudinal study of patients with no diagnosis of depression or anxiety prior to receiving a diagnosis of DED found that with DED treatment, improvements in DED symptoms correlated with improvements in psychological symptoms. 31 In these patients whose psychological symptoms improved when their DED symptoms improved, the burden of living with DED symptoms may have been contributing to their depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that clinical DED diagnosis is regarded as difficult at the best of times, due to discrepancies between signs and symptoms 4749. Furthermore, relatively objective tests such as TBUT, Schirmer test, and lissamine green staining have shown a poor correlation with clinical signs 50,51. Previous population-based studies have assessed the prevalence of DED by symptoms alone5052 and DED symptom assessment has been commonly reported as the foremost diagnostic tool by both optometrists and ophthalmologists 5254.…”
Section: Discussionmentioning
confidence: 99%
“…When the eye does not produce enough tears or when the tears evaporate too quickly, dry eye develops. Keratoconjunctivitis sicca refers to a severe form of dry eye illness [3].…”
Section: Introductionmentioning
confidence: 99%